Penghambat Sertifikasi Halal pada UMKM di Kota Pontianak - Rahmawati, Lusi; Al Kautsar, Rafli; Rahmadani, Suci; Zehriyah, Ainun (Al-fiqh, 2025)
Halal certification is an essential requirement for culinary MSMEs in Pontianak City because the majority of consumers are Muslims who demand guaranteed product halalness. This study aims to analyze the urgency of halal certification and the obstacles faced by MSME operators in fulfilling its requirements. The research employs a descriptive qualitative approach through interviews, observations, and literature studies, which were analyzed using thematic analysis. The results show that halal certification enhances consumer trust, expands market access, and strengthens business competitiveness. However, MSMEs still face several challenges, including limited understanding of the procedures, the perception of high certification costs, complex administrative processes, and minimal assistance from related institutions. Therefore, continuous education, assistance, and more supportive policies are needed so that halal certification can be more easily accessed and contribute to strengthening the halal-based economy in Pontianak City.